Cost‐effectiveness of alternative changes to a national blood collection service. (16th May 2018) - Willis, S.; De Corte, K.; Cairns, J. A.; Zia Sadique, M.; Hawkins, N.; Pennington, M.; Cho, G.; Roberts, D. J.; Miflin, G.; Grieve, R.
SUMMARY: Objectives: To evaluate the cost‐effectiveness of changing opening times, introducing a donor health report and reducing the minimum inter‐donation interval for donors attending static centres. Background: Evidence is required about the effect of changes to the blood collection service on costs and the frequency of donation. Methods/Materials: This study estimated the effect of changes to the blood collection service in England on the annual number of whole‐blood donations by current donors. We used donors' responses to a stated preference survey, donor registry data on donation frequency and deferral rates from the INTERVAL trial. Costs measured were those anticipated to differ between strategies. We reported the cost per additional unit of blood collected for each strategy versus current practice. Strategies with a cost per additional unit of whole blood less than £30 (an estimate of the current cost of collection) were judged likely to be cost‐effective. Results: In static donor centres, extending opening times to evenings and weekends provided an additional unit of whole blood at a cost of £23 and £29, respectively. Introducing a health report cost £130 per additional unit of blood collected. Although the strategy of reducing the minimum inter‐donation interval had the lowest cost per additional unit of blood collected (£10), this increased the rate of deferrals due to low haemoglobin (Hb). Conclusion: The introduction of a donor health report is unlikely to provide a sufficient increase in donation frequency to justify the additional costs. A more cost‐effective change is to extend opening hours for blood collection at static centres.